[Math] Converting from DNF to CNF

logicpropositional-calculus

How to convert a formula from DNF to CNF. Example:

$(A \wedge \neg B) \vee (B \wedge \neg A)$ or similar trivial DNFs?
It thought it could be work with the distributive law. But I don't know how to continue from: $(A \vee ( B \wedge \neg A)) \wedge ( \neg B \vee (B \wedge \neg A))$

Thanks for help!

Best Answer

$$A \lor (B\land \lnot A) = (A \lor B) \land (A\lor \lnot A) = A \lor B$$ and $$\lnot B \lor (B \land \lnot A) = (\lnot B \lor B) \land (\lnot B \lor \lnot A) = \lnot B \lor \lnot A$$